Pengaruh Ukuran Perusahaan Dan Leverage Terhadap Volatilitas Harga Saham Pada Sektor Proterties Real Estate Yang Terdaftar Di Bursa Efek Indonesia - Syarifah Fitria; Yulia Tri Kusumawati; Rahman Anshari (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2025)
This study examine the influence of firm size and leverageon stock price volatility in the property and real estate sector listed on the Indonesia Stock Exchange (IDX) during the 2023-2024 period. Employing a quantitative approach with multiple linear regression analysis and purposive sampling method, the research analyzes 77 companies selected from a total population of 94 sectoral firms meeting the eligibility criteria. The result indicate that firm size has a significant negative effect of stock price volatility, suggesting that larger companies tned to exhibit more stable price fluctuations. In contrast, leverage demonstrates a positive but in significant impact, implying that debt structure does not substantially affeck stock price volatility in this sector. These findings conclude that firm size plays a crucial role in reducting stock price volatility, while leverage does not show significant influence, providing practical implications for investor to consider company scale as an indicator of price stability when making investment decisions in Indonesia’s property.